Application of Statistical Method to Investigate The Effects of Design Parameters on The Performance of Microring Resonator Channel Dropping Filter - Haroon, Hazura; Sahbudin, Saari; P. Susthitha, Menon; Abdul Razak, Hanim (John Wiley & Sons, Ltd, 2013)
Microring resonator (MRR)-based channel dropping filters have been extensively explored because of the high quality factor, compact size, and easy integration of fabrication. In order to design an excellent MRR wavelength filter, optimization of the design parameters are essential. In this paper, the design trade-off ofMRR-based channel dropping filter was statistically studied by employing the Taguchi method. Four control factors considered were width of rings and channels, radii of the microring, upper rib waveguide height, and gap size. The analysis of variancewas adopted to analyze significant trends that occurred on the free spectral range (FSR) and insertion loss (IL) performance under different sets of control factor combinations. The best parametric combination of control factors was identified in order to achieve a balance performance between large FSR and low IL using Finite-Difference Time Domain (FDTD) simulation by RSoft Inc. After optimization, the value of FSR and IL obtained was 17nm and 0.245 dB, respectively. Confirmation tests were carried out to verify the optimized parametric combinations and a new parametric combination considering both outputs were 16nm and 0.215 dB. The optimal combinations were 6 mm ring radius with the separation gap of 50 nm and 350 nm350 nm rib waveguide cross section. Copyright © 2013 John Wiley & Sons, Ltd.